Utilization of anterior segment optical coherence tomography enhanced high resolution corneal in measuring pterygium thickness - Hilmi, Mohd Radzi; Mohd. Kamal, Khairidzan; Che Azemin, Mohd Zulfaezal; Ariffin, Azrin Esmady (Medical Faculty of Sultan Agong Islamic University, 2019)
Introduction: A significant degree of corneal astigmatism can be induced by the encroachment of a pterygium onto a cornea. As various pterygium morphologies have been advocated as contributing factor on corneal astigmatism, little support in the literature available in establishing techniques in measuring pterygium thickness as clinical indicator. To further substantiate claims of establishing measurement of pterygium thickness, the aim of this study was to describe a quantitative method in determining pterygium thickness using anterior segment optical coherence tomography. Methods: Anterior segment imaging was performed using enhanced high resolution cornea of Visante™ optical coherence tomography in 120 primary pterygium eyes. Prior to imaging, corneal topography assessment was performed on each pterygium eye in order to identify its topographic location. Based on topography mapping, three meridians (in degrees) were selected as close as possible to the pterygium border, which signify the demarcation of pterygium from the cornea. Reliability testing between intra and inter-observer of optical coherence tomography imaging modality was examined using intraclass correlation and scatter plot. Results: The overall (n = 120) mean and standard deviation of pterygium thickness via enhanced high resolution cornea of optical coherence tomography modality were 0.48 ± 0.10 mm (confidence interval: 0.45 – 0.50). Optical coherence tomography imaging also showed excellent intra and intergrader reliability in measuring pterygium thickness with intraclass correlation of 0.997 (confidence interval: 0.994 – 0.998). Conclusions: Enhanced high resolution cornea of anterior segment optical coherence tomography imaging is a better choice in assessing pterygium compared to traditional slit-lamp biomicroscopy. This tool is applicable for future work related to better understanding on the role thickness in pterygium morphology, its progression and prediction of induced corneal astigmatism and visual impairment due to pterygium.